PENGARUH LATIHAN ENDURANCE DITINJAU DARI PEMBERIAN UBI JALAR TERHADAP VO2 MAX PADA ATLET BOLA BASKET KABUPATEN PANGKEP - Chaerunnisa Chaerunnisa; Mutmainnah Mutmainnah; Ichsani Ichsani (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
This study is an experimental study (Experimental Research) which aims to determine the effect of endurance training in terms of giving sweet potatoes to VO2 Max in basketball athletes in Pangkep Regency. With the research method (Two Groups Pretest-Posttest Design). The dependent variable is the VO2 Max basketball athlete in Pangkep Regency. The population in this study were all female basketball athletes in Pangkep Regency. Sampling is using purposive sampling. With a sample of 10 people, basketball athletes were the experimental group and the control group was 5 people. The research data were obtained by giving tests and measurements of VO2 Max in the form of Pre-test and Post-test. The data analysis technique is the analysis using the SPSS statistical test. The data analysis technique used is descriptive test, data normality test, and T test. The results of the descriptive test of the experimental group obtained an average VO2 Max in the Pre- Test of 28 and the Post-Test results obtained an average of 36.8 . While the control group obtained results with an average VO2 Max in the Pre-Test of 33.7 and the results of the Post-Test obtained results with an average of 32.6. The results of the normality test of the Pre-Test experimental group obtained the Shapiro-Wilk value, Sig = 0.205 (P > 0.05). Post-Test obtained Shapiro-Wilk value, Sig = 0.998 (P > 0.05). While the Pre-Test Control group obtained the value of Shapiro-Wilk, Sig =0.455 (P > 0.05). Post-Test obtained Shapiro-Wilk value, Sig = 0.884 (P > 0.05). The results of the T-test of experimental group data analysis obtained a Sig value of 0.003 (sig <0.05), with a difference of 8.8, which means that there is a significant effect. While the control group obtained the value of Sig = 0.469 (Sig < 0.05), with a difference (-1), which means there is no significant effect. So it can be concluded that there is an effect of endurance training in terms of giving sweet potatoes to VO2 Max in basketball athletes in Pangkep district.